Accurate Estimation of Upper Limb Orthosis Wear Time Using Miniature Temperature Loggers - Claudia J.W. Haarman; Edsko E.G. Hekman; Johan S. Rietman; Herman van der Kooij (Medical Journals Sweden, 2022)
Objective: To propose and validate a new method for estimating upper limb orthosis wear time using miniature temperature loggers attached to locations on the upper body. Design: Observational study. Subjects: Fifteen healthy participants. Methods: Four temperature loggers were attached to the arm and chest with straps. Participants were asked to remove and re-attach the straps at specified time-points. The labelled temperature data obtained were used to train a decision tree classification algorithm to estimate wear time. The final performance (mean error and 95% confidence interval) of the trained classifier and the wear time estimation were assessed with a hold-out data-set. Results: The trained algorithm can correctly classify unseen temperature data with a mean classification error between 1.1% and 3.1% for the arm, and between 1.8% and 4.0% for the chest, depending on the sampling time of the temperature logger. This resulted in mean wear time errors between 0.5% and 8.3% for the arm, and 0.13% and 13.0% for the chest. Conclusion: The proposed method based on a classifier can accurately estimate upper limb orthosis wear time. This method could enable healthcare professionals to gain insight into the wear time of any upper limb orthosis. LAY ABSTRACT Upper limb orthoses are wearable devices that support the impaired shoulder, arm or hand. As orthoses can be effective only if they are worn, information about wear time will help physicians and therapists to evaluate the effectiveness of their prescribed treatment. Currently, physicians and therapists rely mainly on subjective data from patients, such as diaries or questionnaires, which may be biased and inaccurate. This study developed a new, objective method to estimate wear time, based on temperature readings from miniature sensors that can be attached easily to any upper limb orthosis. The results show that the wear time of upper limb orthoses can be assessed accurately using this method.